Micro-SQUIDs based on MgB2 nano-bridges for NEMS readout. (15th September 2016) - Lolli, L; Li, T; Portesi, C; Taralli, E; Acharya, N; Chen, K; Rajteri, M; Cox, D; Monticone, E; Gallop, J; Hao, L
Abstract: We show the results obtained from the fabrication and characterisation of MgB2 loops with two nano-bridges as superconducting weak links. These ring structures are made to operate as superconducting quantum interference devices and are investigated as readout system for cryogenics NEMS resonators. The nano-constrictions are fabricated by EBL and ion beam milling. The SQUIDs are characterised at different temperatures and measurements of the noise levels have been performed. The devices show high critical current densities and voltage modulations under applied magnetic field, close to the critical temperatures.